The speed and stability of price adjustment in Australian manufacturing - Bloch, Harry; Olive, M. (Blackwell Publishing Asia, 2007)
A model of industry speed of price adjustment is derived from firm pricing behaviour. The model is applied to quarterly two-digit Australian manufacturing data for the period 1985 (Q3) to 2002 (Q3). The results suggest that the industry speed of price adjustment is positively related to the average size of large firms within the industry and is negatively related to industry concentration. We also find that import share has a role is attenuating the effects of industry concentration and that growth in a moving average of real gross domestic product reduces the speed of price adjustment. Calculated industry speeds of price adjustment are both stable across the period of examination and small, suggesting that manufacturing prices are sticky.